PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI ERA KONTEMPORER - Evitayani Tulak; Yonatan Bottong, Julita Bunga Tandi, Mariam Margaretha Irap, Thalita Killa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian Religious Education plays an important role in shaping the character of students through Christian values such as love, honesty, and responsibility. This article analyzes the role of Christian Religious Education in facing the challenges of the contemporary era and effective strategies that can be applied. Literature study is used to explore the concept of character from a Christian perspective, the role of teachers, and the challenges and solutions of implementation. The results of the study indicate that an experiential, technology-based approach, and collaboration with families and churches are essential to increasing the effectiveness of Christian Religious Education. Thus, Christian Religious Education can continue to be a pillar in building the character of the younger generation